2015
DOI: 10.1590/0004-282x20140193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speech therapy and pharmacological treatment in prosody of parkinsonians

Abstract: Objective: Parkinsonian patients usually present speech impairment. The aim of this study was to verify the influence of levodopa and of the adapted Lee Silverman Vocal Treatment 1 method on prosodic parameters employed by parkinsonian patients. Method: Ten patients with idiopathic Parkinson's disease using levodopa underwent recording of utterances produced in four stages: expressing attitudes of certainty and doubt and declarative and interrogative modalities. The sentences were recorded under the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…While PT makes up a large portion of rehabilitation therapies use in patients with PD, studies on the efficacy of OT and ST in the treatment and management of PD have also been done, showing improvements in quality of life, dysarthria, and hypophonia. 2,3,7,9 Up to 89% of patients with PD have speech disorders, yet in this study, only 14.6% received ST consultation or treatment. 18 Likewise, falls are a common indication for PT referral, and occur in up to 68% of patients with PD, 19 but only 14.2% of our cohort received PT/OT.…”
Section: Neurologist Care and Rehabilitation Therapies Utilizationmentioning
confidence: 67%
See 1 more Smart Citation
“…While PT makes up a large portion of rehabilitation therapies use in patients with PD, studies on the efficacy of OT and ST in the treatment and management of PD have also been done, showing improvements in quality of life, dysarthria, and hypophonia. 2,3,7,9 Up to 89% of patients with PD have speech disorders, yet in this study, only 14.6% received ST consultation or treatment. 18 Likewise, falls are a common indication for PT referral, and occur in up to 68% of patients with PD, 19 but only 14.2% of our cohort received PT/OT.…”
Section: Neurologist Care and Rehabilitation Therapies Utilizationmentioning
confidence: 67%
“…Evidence for the efficacy of rehabilitation therapies in the treatment and management of Parkinson disease (PD) has been expanding, demonstrating improvements in function, activities of daily living, speech volume, and quality of life. [1][2][3][4][5][6][7][8][9][10][11] As a result, current American Academy of Neurology (AAN) quality measures for PD treatment advocate for the regular assessment of the need for physical therapy (PT), occupational therapy (OT), and speech therapy (ST). 12 Similar guidelines exist globally, motivating research on the utilization of rehabilitation therapies in PD in other countries (e.g., Germany, United Kingdom, the Netherlands).…”
mentioning
confidence: 99%
“…Over the years, various therapies have been applied to solve dysarthria in PD. A study showed that new behavioral treatment techniques of speech and language therapy seemed to be more effective in improving vocal loudness and speech intelligibility in patients with PD [51][52][53][54] and they also maintained a long-term effect [55]. Patients with PD also have impairment of facial expression [56,57], swallowing and tongue function.…”
Section: Introductionmentioning
confidence: 99%
“…Drug therapy has only modest effects on prosodic aspects of parkinsonian speech, so other therapeutic measures such as speech and language therapy (SLT) could play a role in treatment. [ 5 ] Conventional SLT is tailored to individual patients’ needs and may include: diaphragmatic breathing, pacing/rate control, word-finding strategies, and voice/articulation exercises. [ 6 ] One technique that has been used in PD is attention to effort, where the speaker is asked to produce a loud voice and focus their effort on attaining, monitoring, and maintaining this.…”
Section: Introductionmentioning
confidence: 99%